TREN PEREMPUAN MENGGUGAT CERAI DI KOTA AMBON: SEBUAH PENDEKATAN ANTROPOLOGI FEMINISME - I Nyoman Yoga Segara (Harmoni, 2016)
This research is motivated by a mixed This research was motivated by a response on the release of The Religious Courts (Badan Peradilan Agama), saying that in 2014 there was a significant increase on the divorce rate among Muslims. Over the period of four years (2010-2014), there have been 2 million couples registered their marriages but nearly 300.000 divorce cases or about 15% out of that figure ended up in the religious courts. Surprisingly, 70% of the divorce cases were filed by women, and the remaining were filed by men. The religious courts also release some cases saying that the divorce rate has increased in some other areas. This research questions whether or not the divorce rate in the city of Ambon is also very high. The assumption is that Ambon has no high rate of divorce as the area still maintains local tradition and the traumatic feeling of the past conflict. This research adopts qualitative approach through interview techniques, observation, and focused group discussion. Inspired by the concept of dialectical triad and the Anthropology of feminism as a framework, this study also successfully demonstrates that the divorce trends happen as well in the city of Ambon. The conclusion of this research is; firstly, it is due to physical and non physical violence and the collapse of religious values in marriage that encourage women to ask for divorce. Secondly, there is a lack of response of the social structure, especially the role of the government through Religious Court and Religious Affairs Office (Kantor Urusan Agama). And the thirdly, traditional institutions, such as tiga batu tungku and saudara kawin are fading away. If this last institution operates well it can become an advisory media to preserve the family and the marriage.